Morpheme acquisition in EFL context: Third person singular agreement morpheme -s. - Sari, Irfan; Erisen, Yavuz; Ejder, Ali; Inci, Ersin (ELSEVIER SCIENCE BV, 2015)
Learners of a second language have always been struggling to acquire the 3rd person agreement morpheme -s. The present study investigated the factors, whether over regularization or L1 interference, that EFL learners face while acquiring the of 3rd person agreement morpheme -s. The participants of the current study were 40 elementary level 7th graders students composed of 20 males and 20 females whose ages ranged from 12 to 14 and studying at a state school in Istanbul/Turkey. There were basically two instruments for this study which are written and oral outputs of the learners in the form of in-class and performance assignments. Activities have been prepared carefully to canalize the students to use all the personal pronouns. Oral part of the activities are recorded and each incidences of wrong use of 3rd person agreement morpheme -s counted; and same for writing. The results show that the errors made by students are mostly due to over regularization of the rule and L1 interference is not observed too much. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Language learning; L1 interference; 3rd person agreement morpheme -s; Education & Educational Research; Social Sciences - Other Topics